(untitled) (Vietnam Journal of Community Medicine, 2024)
Objectives: The study aimed to evaluate the analgesic efficacy and adverse effects of erector spinae plane block in video-assisted thoracoscopic surgery for lung resection. Subjects and methods: From July 2023 to September 2024, a cross-sectional descriptive study included 30 patients with indications for video-assisted thoracoscopic surgery for lung resection who received analgesia using unilateral erector spine plane block with catheter insertion at Bach Mai Hospital. When the VAS score was above 4, Ketorolac was added and Morphine titrated as necessary. The primary outcome was VAS pain score (from 0 to 10) at rest and during movement. Some adverse effects were assessed and recorded. Results: The mean VAS scores at rest and during movement at most assessment points in the 72 hours after surgery were below 4 (2.03 ± 0.63 points and 2.76 ± 0.58 points at the 24th hour; 1.97 ± 0.63 points and 2.52 ± 0.51 points at the 48th hour, respectively). Ten patients required ketorolac, and eight patients (26.67%) required morphine titration (mean 541.67 ± 144.34 mcg). There were no serious complications related to the erector spine plane block in this study. Conclusion: Erector spine plane block provides good pain relief after video-assisted thoracoscopic surgery for lung resection, and no serious complications related to this technique were recorded.